Marine Sediment Mixed With Activated Carbon Allows Electricity Production and Storage From Internal and External Energy Sources: A New Rechargeable Bio-Battery With Bi-Directional Electron Transfer Properties - Sudirjo, Emilius; Buisman, Cees J. N.; Strik, David P. B. T. B. (Frontiers in Microbiology, 2019)
Marine sediment has a great potential to generate electricity using a bioelectrochemical system (BES) like the microbial fuel cell (MFC). In this study, we investigated the potential of marine sediment and activated carbon to generate and store electricity. Both internal and external energy supply was validated for storage behavior. Four types of anode electrode compositions were investigated. Two were mixture of different volumes of activated carbon (AC) and mixed with Dutch Eastern Scheldt marine sediment (67% AC, 33% AC) and the others were 100% AC or 100% marine sediment based. Each composition was duplicated. Operating these BES’s under MFC mode with solely marine sediment as the anode electron donor resulted in the creation of a bio-battery system. The recharge time of such bio-battery does depend on the fuel content and its usage. The results showed that marine sediment and activated carbon (AC) were able to generate and store electricity. The 100% AC and the 67% AC mixed with marine sediment electrode were over long term potentiostatic controlled at -100mV vs Ag/AGCl which resulted in a cathodic current and a negative applied voltage. After switching back to MFC operation mode with an external load, the electrode turned into an anode and electricity was generated. This supports our hypothesis that external supply electrical energy was recovered via bi-directional electron transfer. With open cell voltage experiments these AC marine bioanodes showed internal supplied electric charge storage up to 100 mC at short self-charging times (10 and 60 seconds) and up to 2.4 C (3,666 C/m3 anode) when the charging time was increased up to 1 hour. Using a hypothetical cell voltage of 0.2V, this value represents an internal electrical storage density of 0.3 mWh/kg AC marine anode. Furthermore it was remarkable that the BES with 100% marine sediment based electrode also acted like a capacitor similar to the charge storage behaviors of the AC based bioanodes with a maximum volumetric storage of 1,373 C/m3 anode. These insights give opportunities to apply such BES systems as e.g. ex-situ bio-battery to store and use electricity for off-grid purpose in remote areas.